Iktomi Methodology. (March 2023) - White Eyes, Chance
This essay responds to narrative analysis and other Indigenous Methodology skeptics who question the legitimacy of storytelling, oral tradition, and narrative analysis as legitimate forms of data and research. Iktomi Methodology (named after a Lakota character in oral tradition) is not only decolonizing, but is forward thinking, not only documenting what has happened in the past, but what could potentially happen in the future. Iktomi Methodology uses Tribal Critical Theory to legitimize Indigenous storytelling as valid forms of data and analysis of how to treat Indigenous students. The essay then uses a version of narrative analysis that incorporates a specific Native American character that arises often in stories on how to behave when it comes to dealing with challenges, "Iktomi" becomes the vessel through which educators can question current policy and practices to think differently about supporting Indigenous students in postsecondary education.